Digital comics as a communication medium to convey the dangers of mental disorders among victims of bullying and perpetrators of bullying against teenagers at SMK Muhammadiyah 1 Yogyakarta - Sabri, Sabri; Yordan Rismarinandyo, Moch. (Universitas Ahmad Dahlan, 2024)
This study aims to investigates the efficacy of digital comics as a communicative medium to convey the potential dangers of mental disorders to adolescent victims and perpetrators of bullying at SMK Muhammadiyah 1 Yogyakarta. Using the Research and Development (R&D) methodology, the development process followed the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. To validate the developed comic, assessments were conducted by media experts, material experts, students, and teachers at SMK Muhammadiyah 1 Yogyakarta. In addition, this study also used pretest and posttest observations, as well as questionnaires. Data analysis involved normality and homogeneity tests. The results showed a high level of validity for the digital comics, with 87% of media experts rating the digital comics as valid, 95% of material experts rating the digital comics as highly valid, and 76% of language experts rating the digital comics as valid. In addition, teacher and student evaluations yielded very high levels of validity, at 90% and 92% respectively. These findings collectively demonstrate the potential of digital comics to effectively communicate the risks associated with mental disorders in the context of bullying, especially among adolescent victims and perpetrators. This research underscores the importance of digital comics as a valuable tool for mental health education and awareness among adolescents, ultimately contributing to the fostering of more supportive and inclusive school environments.